Sistem Pendukung Keputusan dalam Implementasi RSPO (Roundtable on Sustainable Palm Oil) pada Petani Pola Swadaya di Kabupaten Paser - Bustomi, Muhamad Yazid; Putra, Pandhu Rochman Suosa; Sardianti, Andi Lelanovita; Abidin, Zainal; Lisnawati, Andi; Sukariyan, Sukariyan (Jurnal Agro Industri Perkebunan, 2026)
Implementing RSPO (Roundtable on Sustainable Palm Oil) standards is one way to address the challenges palm oil products face in competing in the global market. The purpose of this study is to identify the factors that support farmers' decisions in implementing RSPO standards. The study was conducted from July to September 2025 in Kertabumi Village, Kuaro District, Paser Regency, with the Bumi Subur cooperative as a partner in the RSPO implementation process. Data collection was conducted through surveys and focus group discussions (FGDs). Data analysis using the Analytic Hierarchy Process (AHP) method was conducted based on the FGD results, which were then weighted by experts comprising academics, supporting institutions, KUDs, independent farmers, and village officials. Decision support factors were arranged in a hierarchy: first, determining the decision objective; then, selecting criteria; and finally, determining decision alternatives. The results of the study show that the criteria with the highest value are environmentally friendly factors (0.249), followed by cultivation according to standards (0.228). After determining the criterion with the highest weight, the next step is to select decision-support alternatives for the environmentally friendly criterion with the highest weight, namely RSPO, which requires protecting high conservation-value areas (0.240). Based on the above, it can be seen that environmentally friendly cultivation is one of the most important factors that encourage farmers to implement RSPO standards, alongside demand for environmentally friendly palm oil products.